O‘QITUVCHILARNI TARIXIY MATERIALLAR VOSITASIDA VATANPARVARLIK RUHIDA TARBIYALASHNING PEDAGOGIK IMKONIYATLARI - Kosbergenov, R.M. (SCIENCE and SOCIETY, 2024)
The article talks about improving the process of educating young people and future teachers in the spirit of patriotism by means of local historical materials and their pedagogical possibilities.